The Mathematical Problem-Solving Processes Of Primary Students - Cahyaningsih, Ujiati; Pangestika, Rintis Rizkia; Mumpuni, Atikah; Prasetyo, Teguh (Papanda Publisher, 2023)
The purpose of this study is to assess the mathematical problem-solving skills of students. Up to three fifth-grade students were selected to represent high, medium, and low mathematical problem-solving skills. This study uses a qualitative approach based on a case study methodology. Data collection methods included examinations, interviews, questionnaires, and records. Triangulation tests were carried out using triangulation procedures, analyzing informants, and designing member checks. The data analysis technique included data collection, reduction, presentation, inference, and verification. The results showed that students with above-average abilities can deal effectively with challenges. Pupils of average ability can only reach the planning stage, and when it comes to carrying out the plan, they often make mistakes in entering numbers and performing calculations.